The modulation of endothelial glycocalyx by sulodexide on the porcine model of enzymatic endothelial glycocalyx damage - a pilot study - Astapenko, David; Gorskaja, Diana; Zrzavecky, Marek; Kawashima, Hanako; Ssali, Edward; Navratil, Pavel; Hana, Ludek; Motesicky, Jan; Radochova, Vera; Hyspler, Radomir; Ticha, Alena; Lehmann, Christian; et al. (Clinical hemorheology and microcirculation, 2025)
BackgroundSulodexide is a glycosaminoglycan-based drug prescribed to patients with angiopathy. We performed a pilot study to investigate whether sulodexide positively modulates the endothelial glycocalyx (EG) layer and the microcirculation in a porcine model of EG enzymatic damage. The EG is a sugar-based endothelial lining that is involved in the physiology of the capillary wall and the pathogenesis of many diseases.MethodsEG damage was induced in eight piglets by hyaluronidase III and heparanase I given intravenously. Four animals received sulodexide 600 IU intravenously before the enzymes and four animals after the enzymes were administered. Four animals constituted a control group. Sublingual microcirculation by side-stream dark field imaging and plasmatic concentration of syndecan-1 by ELISA were measured at baseline, 20 min after intervention, and at the 40th, and 60th minute onwards. The statistics were performed with a one-way ANOVA test with Turkey's correction for multiple comparisons testing. Timepoint comparison was performed by Student t-test or Mann-Whitney test.ResultsAt baseline, there were no statistically significant differences between the animal groups. After the intervention, the levels of syndecan-1 were significantly lower in the control group. While there were no differences between the two intervention groups. The sublingual microcirculation analysis showed that the DeBacker score was significantly higher in the control group. At 60 min, there was also a statistically significant difference in DeBacker score between the groups (8.1 ± 1.6 mm-1 in the group with enzymes given first and 11 ± 0.92 mm-1 in the group with sulodexide given first, p = 0.03). The analysis of the proportion of perused vessels did not show any statistically significant differences.ConclusionThe results of the study demonstrated a working model of EG damage but no specific action of sulodexide on EG modulation. In the sublingual microcirculation analysis, the sulodexide reduced the fall in absolute tissue perfusion in 60 min.
Keywords: Disease Models, Animal; prasata; Animals; Glycosaminoglycans; Microcirculation; glykokalyx; glykosaminoglykany; Syndecan-1; modely nemocí na zvířatech; Pilot Projects; syndekan-1; Glycocalyx; zvířata; cévní endotel; pilotní projekty; Hyaluronoglucosaminidase; Endothelium, Vascular; Swine; mikrocirkulace; hyaluronoglukosaminidasa